2005
DOI: 10.1080/13550280500385310
|View full text |Cite
|
Sign up to set email alerts
|

Glycoprotein-mediated induction of apoptosis limits the spread of attenuated rabies viruses in the central nervous system of mice

Abstract: Induction of apoptosis by rabies virus (RV) has been reported to be associated with the expression of the glycoprotein (G), but inversely correlated with pathogenicity. To further delineate the association between the expression of the G and the induction of apoptosis, recombinant RVs with replacement of only the G gene were used to infect mice by the intracerebral route. Recombinant viruses expressing the G from attenuated viruses expressed higher level of the G and induced more apoptosis in mice than recombi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
47
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 40 publications
10
47
0
Order By: Relevance
“…These data suggest that suppression of apoptosis plays an important role in the pathogenicity of CE(NiM95) strain. Many previous studies have demonstrated that RABV G protein plays an important role in induction of apoptosis with a close relation to the attenuated phenotype [7,11,12]. The results of this study, taken together with our previous data [10], suggest that apoptosis induced by an M protein-mediated mechanism is also inversely correlated with viral pathogenicity.…”
supporting
confidence: 73%
See 2 more Smart Citations
“…These data suggest that suppression of apoptosis plays an important role in the pathogenicity of CE(NiM95) strain. Many previous studies have demonstrated that RABV G protein plays an important role in induction of apoptosis with a close relation to the attenuated phenotype [7,11,12]. The results of this study, taken together with our previous data [10], suggest that apoptosis induced by an M protein-mediated mechanism is also inversely correlated with viral pathogenicity.…”
supporting
confidence: 73%
“…Results of many previous studies support this idea by demonstrating an inverse correlation between pathogenicity and apoptosis-inducing ability of RABV [7,11,12]. More specifically, Jackson et al [7] reported that, compared to virulent SAD-L16 strain, the attenuated mutant SAD-D29 strain strongly induces apoptosis in neurons in the infected mouse brain, resulting in inefficient spread of infection in the brain.…”
supporting
confidence: 68%
See 1 more Smart Citation
“…Recombinant CVSB2c expressing G [B2c(DRV-G)] or P [B2c(DRV-P)] from DRV-Mexico was constructed as described previously (35,36). Virus stocks were prepared in 1-day-old suckling mice as described previously (37). When moribund, mice were euthanized and brains removed.…”
mentioning
confidence: 99%
“…Studies have shown that attenuated RABVs appeared to activate, while pathogenic RABVs evaded, the host innate immune responses, and the evasion was due to the restricted expression of the G protein [28,33]. In street RABV strains, G protein expression is more controlled than in attenuated strains [24,37].…”
Section: Introductionmentioning
confidence: 99%